Folate supplementation in patients with psoriasis treated with methotrexate - effect on safety and efficacy - Magdalena Żychowska; Aleksandra Batycka-Baran; Andrzej Bieniek; Wojciech Baran (Termedia Publishing House, 2014)
Methotrexate (MTX) is commonly used in dermatology, mainly in patients with psoriasis and psoriatic arthritis. Gastrointestinal disorders, mouth ulcerations, malaise, hair loss, hepatic dysfunction and bone marrow suppression are the most common adverse effects of MTX therapy. The occurrence of side effects is suggested to be the main reason for discontinuation of the therapy. Supplementation with folates seems to be a good strategy in limiting adverse effects; however, excessive doses may decrease the efficacy of MTX therapy. Currently, there are no consistent recommendations for folate supplementation in psoriatic patients. An extensive PubMed search (1960 - March 2014) revealed only a few studies, with one randomized controlled trial concerning the impact of folate supplementation in patients with psoriasis. These studies support the protective effect of folate supplementation and suggest that folic acid may reduce gastrointestinal disturbances. Further research, including randomized controlled trials, should be performed.